Intranasal Neuropeptide Y as a Potential Therapeutic for Depressive Behavior in the Rodent Single Prolonged Stress Model in Females - Nahvi, Roxanna J.; Tanelian, Arax; Nwokafor, Chiso; Hollander, Callie M.; Peacock, Lauren; Sabban, Esther L. (Frontiers in Behavioral Neuroscience, 2021)
The susceptibility to stress-elicited disorders is markedly influenced by sex. Women are twice as likely as men to develop posttraumatic stress disorder (PTSD), depression, anxiety disorders, and social impairments following exposure to traumatic stress. However, most of the studies in animal models examining putative therapeutics for stress-triggered impairments, including single prolonged stress (SPS), were performed predominantly with males. Previous studies in males demonstrated that intranasal neuropeptide Y (NPY) can provide therapeutic relief of many SPS-triggered behaviors, but is ineffective in females at the same dose. Thus, females may need a higher dose of exogenous NPY to attain a therapeutically significant concentration since the overwhelming majority of studies found that NPY levels in females in many brain regions are lower than in male rodents. Here, we examined SPS as an appropriate model to elicit many PTSD-associated symptoms in females and whether intranasal NPY at higher doses than with males is able to alter the development of SPS-triggered behavioral impairments. Sprague Dawley female rats were exposed to SPS only, or in a separate cohort after SPS stressors were immediately infused intranasally with one of several doses of NPY, starting with 600ug/rat - 4 times the dose effective in males. In a third cohort of animals, females were infused intranasally with either 600μg NPY, omarigliptin (a dipeptidyl peptidase IV [DPP4] inhibitor), or both right after the SPS stressors. After 19 days they were tested on several behavioral tests. SPS elicited significant depressive/despair like behavior on the forced swim test (FST), anxiety behavior on the elevated plus maze (EPM), as well as impaired social interaction. On the FST, there was a dose-response effect of intranasal NPY, with 1200µg, but not 600µg, preventing development of the SPS-elicited depressive-like behavior. The omarigliptin and 600µg NPY combined treatment, but neither alone, was also sufficient at preventing depressive-like behavior on the FST. The results demonstrate that: (1) SPS elicits several behavioral manifestations of PTSD in females; (2) early intervention with a high dose of intranasal NPY has therapeutic potential also for females; (3) NPY cleavage by DPP4 may play a role in the higher dose requirement for females.